Penerapan Modul Bahasa Mandarin 学习汉语 dengan Project Based Learning Untuk Meningkatkan Keterampilan Berbicara Siswa Kelas XII AK SMK Prapanca 2 Surabaya - Novia Khoirun Nisaa; Kisyani Laksono; Agusniar Dian Savitri (LP. Ma'arif Janggan Magetan, 2023)
This research is a class action research (CAR) combined with the results of the design of teaching material products in the form of a Mandarin Language Module. Researchers tried to use self-made Mandarin language modules to improve students' speaking skills by collaborating using the application of the Project-Based Learning model. The Pre-cycle Test, Cycle 1 Test and Cycle 2 Test use the same test questions by testing students' speaking skills through dialogue displayed on the LCD as discussion material for making projects that can be developed by students in their respective groups. At the pre-cycle stage, 5 students were in the complete category (18.5%) and 22 were incomplete (81.5%). At the stage of cycle I, the percentage of completeness increased to 12 students who were in the complete category (44.5%) and 15 students who did not complete (55.5%). The percentage of each cycle increased until the final results were obtained from cycle 2, namely 92.6% complete (25 students) and 7.4% incomplete (2 students). This result is very satisfying to the researcher because the Mandarin language skill is a subject that is quite difficult for beginners, especially since they have very little study time but are required to master quite a lot of pronunciation and vocabulary.